2021
DOI: 10.1371/journal.pone.0256480
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and clinical features of pulmonary embolism in patients with AE-COPD: A meta-analysis and systematic review

Abstract: Background The prevalence of pulmonary embolism (PE) in the acute exacerbation of chronic obstructive pulmonary disease (AE-COPD) is highly controversial. We conducted a systematic review and meta-analysis to summarize the epidemiology and characteristics of PE with AE-COPD for current studies. Methods We searched the PubMed, EMBASE, Cochrane Library and Web of Science databases for studies published prior to October 21, 2020. Pooled proportions with 95% confidence intervals (95% CIs) were calculated using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…In a meta-analysis comprising 3170 patients admitted for acute exacerbation of COPD, there was a high prevalence of PE and DVT in this clinical profile (pooled prevalence, 17.2% [95% CI, 13.4%–21.3%] and 7.1% [95% CI, 3.7%–11.4%], respectively). 8…”
Section: Venous Thromboembolism (Deep Vein Thrombosis and Pulmonary E...mentioning
confidence: 99%
“…In a meta-analysis comprising 3170 patients admitted for acute exacerbation of COPD, there was a high prevalence of PE and DVT in this clinical profile (pooled prevalence, 17.2% [95% CI, 13.4%–21.3%] and 7.1% [95% CI, 3.7%–11.4%], respectively). 8…”
Section: Venous Thromboembolism (Deep Vein Thrombosis and Pulmonary E...mentioning
confidence: 99%
“…Thus, the above-mentioned factors may lead to a varied amount of literature that meets the requirements in a similar search period. Recently published meta-analyses of AECOPD combined with PE reported a prevalence of 17.2 and 12.9%, respectively ( 48 , 49 ). We included 20 studies involving 5,854 people, higher than those included in the two recently published papers.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, they have little information about the related symptoms, signs, and risk factors ( 68 ). Recently, Fu et al also reported the clinical features of AECOPD combined with VTE ( 48 ). Furthermore, following anticoagulant therapy, there was no significant difference in the risk of recurrent VTE, compared with those without COPD ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis involving 3,170 AECOPD patients showed that the prevalence of PTE and DVT in AE-COPD patients was 17.2% and 7.1%, respectively. 21 However, the link between fibrinogen and DVT/PTE is unclear, since Watz et al found that fibrinogen was inversely associated with levels of physical activity, 14 and the lack of physical exertion is itself a risk factor of the development of DVT/PTE. AECOPD patients tend to have reduced physical exercise due to respiratory dysfunction and/or muscle weakness, which could partly contribute to higher levels of fibrinogen.…”
Section: Discussionmentioning
confidence: 99%